The relationship of α-hydroxybutyrate dehydrogenase with 1-year outcomes in patients with intracerebral hemorrhage: A retrospective study - Limin, Zhang; Alsamani, Rasha; Jianwei, Wu; Yijun, Shi; Dan, Wang; Yuehong, Sun; Ziwei, Liu; Huiwen, Xu; Dongzhi, Wang; Xingquan, Zhao; Guojun, Zhang (Frontiers in Neurology, 2022)
Background and aims: Cardiac enzymes are recognized as a valuable tool for predicting the prognosis of various cardiovascular diseases. The prognostic value of alpha-hydroxybutyrate dehydrogenase (α-HBDH) in patients with intracerebral hemorrhage (ICH) was ambiguous and not evaluated. Methods: Two hundred and thirteen Chinese ICH patients participated in the study from December 2018 to December 2019. Laboratory routine tests and cardiac enzymes, including α-HBDH level, were examined and analyzed. All the patients were classified into two groups by the median value of α-HBDH: B1 < 175.90 and B2≥ 175.90 U/L. The clinical outcomes included functional outcome (according to modified Rankin Scale (mRS) score≥ 3), all-cause death, and recurrent cerebro-cardiovascular events one year after discharge. Associations between the α-HBDH and the outcomes were evaluated using logistic regression analysis. Univariate survival analysis was performed by the Kaplan-Meier method and log-rank test. Results: Of the 213 patients, 117 had α-HBDH ≥175.90 U/L. Eighty-two patients had poor functional outcomes (mRS ≥ 3). During the one-year follow-up, a total of 20 patients died, and 15 of them had α-HBDH ≥ 175.90 U/L during the follow-up time. Moreover, 24 recurrent events were recorded. After adjusting confounding factors, α-HBDH (≥175.90) remained an indicator of poor outcome (mRS 3-6), all-cause death, and recurrent cerebro-cardiovascular events. The ORs for B2 versus B1 were 4.77(95% CI: 2.60 to 8.78, (P=0.001), 2.63 (95% CI: 0.80 to 8.59, P value=0.11) and 2.40 (95% CI: 0.82 to 7.02, P value=0.11) for poor functional outcomes with mRS ≥ 3, all-cause death and recurrent cerebro-cardiovascular events, respectively. Conclusion: Increased α-HBDH at admission was independently related to poor functional outcome and all-cause mortality in ICH patients at one-year follow-up.